TI_GERICHTE 12.2007.77 vom 24. Juli 2007 , Compravendita - garanzia per difetti - errore - dolo - onere della prova - TI Tribunale d'appello (2007)
Compravendita - garanzia per difetti - errore - dolo - onere della prova